Studies on Schismatoglottideae (Araceae) of Borneo LXVII: Bucephalandra danumensis, a new species from Sabah, Malaysian Borneo - Sin, Yeng Wong; Peter C. Boyce; Kartini Saibeh (2018)
Bucephalandra danumensis is described from the Danum Valley Conservation Area, Tawau, Lahad Datu, Sabah, where it is restricted to streams and waterfalls on igneous outcrops in forests on Cretaceous deepwater sediments, and compared with the only other Sabahan Bucephalandra species, and with all species with echinate/papillate spadix appendix staminodes. Recognition of B. danumensis takes Bucephalandra to 31 described species, of which just two, both endemic, are known from Sabah. Both Bucephalandra species from Sabah are illustrated from living plants, and a comparative plate of the spadix of all species with echinate/papillate appendix staminodes is provided.